Hierarchical data partition defence against co-resident attacks. (21st November 2022) - Tian, Junfeng; Wang, Zilong; Li, Zhen
Co-resident attacks are one of the most dangerous types of attack in the cloud environment, posing a great threat to data security and survivability for users. The existing data partition-based and data backup solutions provide users with higher storage overhead while improving the data security and survivability for users. A hierarchical data partitioning scheme is proposed that enables the multilevel partitioning of the data and makes the data have a certain order, which improves the security of user data while facilitating data management. At the same time, through the encrypted data backup, under the premise of improving the survivability of the user's data, the user's storage overhead is reduced. Finally, experiments prove that the proposed scheme improves the data security and survivability and reduces the user's storage overhead.